Draft Annual Plan 1993-94 Vol—III Government of Tripura - Planning Commission (Planning Commission, 1993)
I.R.D.P. has been under implementation in the State since 1980-81 as a centrally Sponsored Scheme funded by Central Government and State Government on 50:50 basis with the objective of lifting the weaker section of Rural population above the poverty line providing income generating activities through Bank's loan and Government subsidy through packages of schemes.
Planning and Coordination Department, Government of Tripura